(untitled) (Bangladesh Critical Care Journal, 2020)
Background and Objective: Diabetes Mellitus has emerged as a major public health problem globally and uncontrolled diabetes mellitus plays important role to develop micro and macro vascular complications. So the present study is done to determine the prevalence of uncontrolled diabetes and to predict the HbA1c from the fasting plasma glucose (FPG) level for Type 2 diabetes mellitus (T2DM) patients. Method: Cross-sectional study was conducted in adult out-patients department of BIRDEM Hospital, Dhaka from January 2019 to June 2019. Data were collected from diabetes guide book of patients who had tested FPG and HbA1c from the same blood sample. For determining the relationship between FPG and HbA1c, linear regression equation was used. Result: A total of 554 T2DM patients were taken for this study. Of the total participants, male and female were 52.1% and 47.9% respectively. Mean±SD of age, FBG and HbA1c were 51.6±10.51 years, 10.89±4.14 mmol/L and 8.83±1.82% respectively. According to this study prevalence of controlled HbA1c (≤7.0%) and FPG (≤7.2mmol/L) were 16.6% and 18.6% respectively by ADA criteria. The prediction model between HbA1c and FPG, expressed as HbA1c=5.369+0.32 FPG (R2 = 0.529, p<0.001) in the study subjects. The study found that the HbA1c level increased by approximately 0.32% per increment of 1.0 mmol/L in FPG. Conclusions: The authors observed that the prevalence of uncontrolled HbA1c (>7.0%) and FPG (>7.2mmol/L) were 84.7% and 81.9% respectively based on ADA criteria. The study also concluded that HbA1c level could be predicted from FPG by using regression equation. Bangladesh Crit Care J March 2020; 8(1): 33-36